1980
DOI: 10.1136/ard.39.4.406
|View full text |Cite
|
Sign up to set email alerts
|

Angioimmunoblastic lymphadenopathy associated with polyarthritis.

Abstract: SUMMARY A patient with angioimmunoblastic lymphadenopathy with dysproteinaemia is described. The patient had a severe clinical illness with a pronounced haemolytic anaemia, which followed well-established polyarthritis and gold therapy. It was accompanied by in-vitro evidence of suppressed cell-mediated immune responses and by development of serum antismooth muscle antibodies. These features are unusual and support theories that this disease has an immunological basis. Improvement occurred with prednisone and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…From x-ray data that were available in 10 cases, bone erosions were reported only in one case by McHugh et al 8 In 3 cases (30%), there was soft tissue swelling, whereas in 6 cases (60%), the x-rays were normal. Subcutaneous nodules were reported in another case by Rothwell et al, 12 but similar to our case, there has not been any histologic analysis of these nodules. The arthritis most commonly involved the small joints of the hand (MCPs, PIPs), wrists, knees, and ankles ( Table 1).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…From x-ray data that were available in 10 cases, bone erosions were reported only in one case by McHugh et al 8 In 3 cases (30%), there was soft tissue swelling, whereas in 6 cases (60%), the x-rays were normal. Subcutaneous nodules were reported in another case by Rothwell et al, 12 but similar to our case, there has not been any histologic analysis of these nodules. The arthritis most commonly involved the small joints of the hand (MCPs, PIPs), wrists, knees, and ankles ( Table 1).…”
Section: Discussionsupporting
confidence: 83%
“…2 A review of the English literature revealed 16 additional patients with well-described synovitis (see Table 1). [2][3][4][5][6][7][8][9][10][11][12][13][14] Although AITL affects equally men and women, AITL-associated arthritis seems to be slightly more common in women (59%, 10 of 17). The majority of patients were middle-aged (mean age, 57.4 years), and their arthritis typically appeared either concurrently with the onset (11 of 17) or during the course (2 of 17) of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seronegative, inflammatory polyarthritis is an unusual feature of immunoblastic lymphadenopathy (IL) (1)(2)(3). Synovianalyses in 2 patients (I ,2) showed inflammatory effusions with a polymorphonuclear cell predominance.…”
Section: To the Editormentioning
confidence: 99%
“…7 A paraneoplastic polyarthritis in association with AITL is uncommon. [8][9][10][11][12] It usually involves the proximal interphalangeal, metacarpophalangeal, wrist, ankle, foot, and knee joints.…”
Section: Case Reportmentioning
confidence: 99%